A methodology for designing thermodynamic energy conversion systems in industrial mass/heat integration problems based on MILP models. (15th October 2019) - Wissocq, Thibaut; Ghazouani, Sami; Le Bourdiec, Solène
Abstract: The integration of thermodynamic systems in industrial processes can help increasing the energy recovery and provide more integration opportunities. However, designing such technologies in a simultaneous mass and heat integration is a large-scale and complex problem. Indeed, the heat requirements created by the mass allocation network are unknown prior to the whole design. Besides, designing sequentially the mass allocation network (MAN) and the heat exchanger network (HEN) can lead to sub-optimal solutions. This paper proposes a three-step methodology based on mixed-integer-linear-programming (MILP) models to evaluate economically suitable technologies, reducing strongly the computational time. After a preliminary step, a first MILP model evaluates economically a great number of technologies simultaneously. In this model, the simplified total cost, including thermodynamic systems capital costs, is minimized. Then, the best thermodynamic systems candidates are identified and used in a second MILP solving the larger problem including the simultaneous MAN and HEN design. The performances of the methodology are assessed on an ammonia recovery case study: 3 economically relevant technologies among 74 are selected in a few seconds. Then, the MAHEN (mass allocation and heat exchange network) is designed with these technologies, showing a decrease of total annualized cost of 3.6%. Highlights: Thermodynamic energy conversion system models, described by temperature levels. Methodology to select thermodynamic systems in mass/heat integration problem. A 1st MILP selects economically relevant systems. A 2nd MILP designs mass allocation and heat exchangers networks including selected systems. Computational and energy performances are assessed on a case study.